Mengoptimalkan Penggunaan Teknologi untuk Pemasaran Aksesoris HP Anggota ONC Melalui Platform Digital - sholeh, muh ibnu sholeh (JIK-PkM: Jurnal Inovatif dan Kreatif hasil Pengabdian kepada Masyarakat, 2024)
This Community Service (PKM) project aims to optimize the use of technology in marketing cellphone accessories carried out by members of the Ngunut Community Outlet (ONC) via digital platforms. ONC, as a local business forum, has great potential to utilize advances in information technology to increase product visibility and competitiveness in an increasingly digital market. Through an Asset-Based Community Development (ABCD) approach, the project engages ONC members in intensive training to improve their technology skills, especially in managing social media and e-commerce platforms. Project stages include identifying community needs and potential, technology skills training, market analysis, digital platform development, and marketing of attractive digital content. By utilizing collaboration with local digital marketing experts, this project aims to achieve a significant increase in sales of HP accessories through digital platforms. The results of this project are expected to not only include ONC business growth but also have a positive impact on the economic empowerment of local community members. Through technology integration and active participation of community members, this project seeks to realize digital marketing that is sustainable and competitive, in line with developing business trends in the digital era.